1999
DOI: 10.1007/s100510050642
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic excitations in the quantum spin system KCuCl

Abstract: KCuCl3 is a three-dimensional coupled spin-dimer system and has a singlet ground state with an excitation gap ∆/kB = 31 K. High-field magnetization measurements for KCuCl3 have been performed in static magnetic fields of up to 30 T and in pulsed magnetic fields of up to 60 T. The entire magnetization curve including the saturation region was obtained at T = 1.3 K. From the analysis of the mag-netization curve, it was found that the exchange parameters determined from the dispersion relations of the magnetic ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
104
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(114 citation statements)
references
References 0 publications
10
104
0
Order By: Relevance
“…Whatever the precise structure may turn out to be, a magnetic-field induced ordering transition can occur in all anisotropic spin systems with a singlet-triplet excitation gap, including weakly coupled Ising-like chains, spin-Peierls chains, and ensembles of spin dimers. Other possible candidate materials with spin gaps include KCuCl 3 [8], CuGeO 3 [9], α ′ − NaV 2 O 5 [10], and the homologous series of cuprates Sr n Cu n+1 O 2n+1 [11].…”
Section: Introductionmentioning
confidence: 99%
“…Whatever the precise structure may turn out to be, a magnetic-field induced ordering transition can occur in all anisotropic spin systems with a singlet-triplet excitation gap, including weakly coupled Ising-like chains, spin-Peierls chains, and ensembles of spin dimers. Other possible candidate materials with spin gaps include KCuCl 3 [8], CuGeO 3 [9], α ′ − NaV 2 O 5 [10], and the homologous series of cuprates Sr n Cu n+1 O 2n+1 [11].…”
Section: Introductionmentioning
confidence: 99%
“…2 In these case, antiferromagnetic order perpendicular to the field appears simultaneously with magnetization parallel to the field, creating field-induced magnetic order, 6 which can be interpreted as a condensation of the lowest lying magnon mode. 7,8,9,10,11,12,13,14,15 In contrast to these case, when the interaction energy dominates, magnetization plateaus can appear accompanied by a magnetic superlattice. 16 Such plateaus have been observed at a rational fraction of the saturation moment.…”
mentioning
confidence: 99%
“…The magnetic ground state is the spin singlet with the excitation gap Δ/k B ≈ 7.5 K. 8,9) The magnetic excitations in TlCuCl 3 were investigated by Oosawa et al, 10) who found that the lowest excitation occurs at Q = (0, 0, 1) and its equivalent reciprocal points, as observed in KCuCl 3 . 11,12) The origin of the gap is the strong antiferromagnetic interaction J = 5.26 meV on the planar dimer Cu 2 Cl 6 in the double chain. The * E-mail: tanaka@lee.phys.titech.ac.jp neighboring dimers couple magnetically along the chain and in the (1, 0, −2) plane.…”
mentioning
confidence: 99%